EKSPLORASI NUANSA SEMANTIK DARI رحمة DAN رحمت DALAM WACANA AL-QUR’AN: SEBUAH STUDI BERBASIS KORPUS - Muhammad Ibnu Pamungkas; Eri Kurniawan; Rinaldi Supriadi (UIN Sunan Gunung Djati Bandung, 2026)
The Qur'an contains numerous near-synonymous lexical items whose meanings vary according to their linguistic and contextual environments. However, corpus-based investigations of these subtle semantic distinctions remain limited. This study examines the lexical forms رحمة and رحمت, which derive from the same root (ر-ح-م) but differ in orthographic realization and syntactic construction, to identify their contextual distribution and semantic functions in the Qur'an. A qualitative descriptive corpus linguistics approach was employed using AntConc to analyse 108 Qur'anic occurrences, comprising رحمة (n = 71) and رحمت (n = 37). The analysis focused on frequency, collocation, and concordance patterns to examine differences in contextual usage. The findings indicate that رحمة occurs across a wider range of semantic contexts referring to divine mercy in a general sense, whereas رحمت predominantly appears in iḍāfah constructions that express possession and constrain meaning according to the surrounding context. These findings demonstrate that the distinction between the two forms is primarily distributional and functional rather than merely lexical or orthographic. This study contributes to Qur'anic lexical semantics by providing corpus-based evidence of contextual variation in near-synonymous expressions and demonstrates the usefulness of corpus linguistics for context-sensitive semantic analysis. The findings also offer pedagogical implications for teaching Qur'anic Arabic by enabling learners to understand lexical meaning through authentic patterns of Qur'anic usage.